Connecting ecosystem services science and policy in the field. Issue 9 (9th August 2021) - Ruhl, JB; Salzman, James; Arnold, Craig Anthony; Craig, Robin; Hirokawa, Keith; Olander, Lydia; Palmer, Margaret; Ricketts, Taylor H
Abstract : Conservation and provision of ecosystem services (ES) have been adopted as high‐level policy in many countries, yet there has been surprisingly little application of these broad policies in the field; for example, ES are rarely considered in permit issuance or other discrete agency actions. This large implementation gap arises in part because the science that drove general policy interest in ES differs from the science needed for practical application. A better understanding of the environmental policy toolkit can guide more effective research to support agency decisions. Here, we outline the framework used to teach environmental policy instruments through the "Five P's": prescription, property, penalty, payment, and persuasion. We then discuss the discrete ES research required to effectively implement each tool. To support greater conservation of ES in the field, scientists and policy makers must clearly recognize what each needs from the other.